PENGAKUAN EKS PARASIT LAJANG KARYA AYU UTAMI BERDASARKAN PERSPEKTIF JUNG - Khoirun Nisak (Universitas Wijaya Kusuma Surabaya, 2019)
This research aims to obtain a description of objectively the dynamics of the main figure in the perspective Jung based on personality which is in novel “Pengakuan Eks Parasit Lajang” creation Ayu Utami. This study using the qualitative research with the hermeneutic and researchers as a key metric. assisted by gathering data. Data is collected from unit-unit the text which reflect the majority of dynamics in the relationship between the personality of top leaders of the banned in a novel “Pengakuan Eks Parasit Lajang” creation Ayu Utami. The internal factors encourage the dynamics of personality the main figure is psychic energy (the libido) of encouragement (drive) and volition ( will ) that is spatially dynamic and work simultaneously to wholeness personal. External factors that encourage the dynamics of personality the main figure is the environment social the main figure in especially factors social environment primary namely figure family .